Sublay repair for primary superior lumbar hernia with the Kugel patch. Issue 5 (24th March 2020) - Lin, Ronggui; Teng, Tianhong; Lin, Xianchao; Lu, Fengchun; Yang, Yuanyuan; Wang, Congfei; Chen, Yanchang; Huang, Heguang
Abstract: Background: A superior lumbar hernia is a posterior ventral hernia that is rarely encountered in the clinical setting. However, no standard operative strategy exists for superior lumbar hernia repair at present. Methods: Twelve patients with primary superior lumbar hernia who underwent sublay repair via the retroperitoneal space with the Kugel patch between December 2008 and June 2019 were included in this study. The demographic, peri‐operative and post‐operative data of the patients were collected to analyse the effectiveness of this technique. Results: All patients underwent an uneventful operation. The median operative time was 60 min, and the median blood loss was 35 mL. The median hernia defect area was 16 cm 2 . Five medium‐sized Kugel patches (11 cm × 14 cm) and seven large‐sized Kugel patches (14 cm × 17 cm) were used for the repairs. The median visual analogue scale score on post‐operative day 1 was 3. The median time to removal of drainage was 3 days. The median duration of the hospital stay was 3 days. No serious post‐operative complications, including seroma, haematoma, incision or mesh infection, recurrence and chronic pain, occurred during the follow‐up period. Conclusion: Sublay repair for primary superior lumbar hernia with the Kugel patch shows benefits including a reliable repair, minimal invasiveness and few post‐operative complications. Abstract : Repair for superior lumbar hernias is technically challenging. Sublay repair using the Kugel mesh is a feasible and effective method for superior lumbar hernias. Sublay repair for superior lumbar hernias provides the advantages of reliable repair and rapid recovery.